1999
DOI: 10.1128/iai.67.3.1086-1092.1999
|View full text |Cite
|
Sign up to set email alerts
|

The Staphylococcal Transferrin-Binding Protein Is a Cell Wall Glyceraldehyde-3-Phosphate Dehydrogenase

Abstract: Staphylococcus aureus and Staphylococcus epidermidis possess a 42-kDa cell wall transferrin-binding protein (Tpn) which is involved in the acquisition of transferrin-bound iron. To characterize this protein further, cell wall fractions were subjected to two-dimensional sodium dodecyl sulfate (SDS)-polyacrylamide gel electrophoresis blotted, and the N-terminus of Tpn was sequenced. Comparison of the first 20 amino acid residues of Tpn with the protein databases revealed a high degree of homology to the glycolyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
62
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(67 citation statements)
references
References 38 publications
4
62
1
Order By: Relevance
“…Enzymatic activity studies of recombinant S. cerevisiae GAPDH3 showed that the apparent K NAD is 686 lM (Fig. 1A), which is close to the value reported for homologous GAPDHs (19). This result indicated that the recombinant GAPDH3 was correctly folded and had biological activity.…”
Section: Rna Recognition Properties Of Gapdh3supporting
confidence: 80%
“…Enzymatic activity studies of recombinant S. cerevisiae GAPDH3 showed that the apparent K NAD is 686 lM (Fig. 1A), which is close to the value reported for homologous GAPDHs (19). This result indicated that the recombinant GAPDH3 was correctly folded and had biological activity.…”
Section: Rna Recognition Properties Of Gapdh3supporting
confidence: 80%
“…In Mycoplasma genitalium, surface-associated GAPDH was shown to be important for adhesion to human mucin (Alvarez et al, 2003). In Streptococcus pyogenes and Candida albicans surface-associated GAPDH was shown to bind to fibronectin (Pancholi and Fischetti, 1992;Gozalbo et al, 1998) and in Staphylococcus aureus the cell wall transferrin-binding protein was found to be GAPDH (Modun and Williams, 1999). GAPDH was also reported to be a virulence-associated immunomodulatory protein in Streptococcus agalactiae (Madureira et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…(2003) reported enzymatically active GAPDH is capable of binding to cytoskeletal and extra‐cellular matrix proteins and is expressed on the surface of group B Streptococcus . Surface‐localized GAPDH of Staphylococcus aureus and Staphylococcus epidermidis bind transferrin (Modun & Williams 1999), whereas the GAPDH of Candida albicans binds fibronectin and laminin (Gozalbo et al . 1998).…”
Section: Discussionmentioning
confidence: 99%